"Care is not care if it isn't person‐centred": A content analysis of how Person‐Centred Care is expressed on Twitter. (28th January 2021) - van Diepen, Cornelia; Wolf, Axel
Abstract: Background: Person‐Centred Care (PCC) has been the subject of growing interest in recent decades. Even though there is no conceptual consensus regarding PCC, many health‐care institutions have implemented elements into their care. Objective: This study aimed to investigate the PCC topics presented by different stakeholder groups on Twitter and to explore the perceptions of PCC within the content of the tweets. Method: Tweets with mentions of PCC in various translations were collected through a Twitter Application Programming Interface in October 2019. The tweets were analysed using quantitative and qualitative content analysis. Results: Five stakeholder groups and ten topics were identified within 1540 tweets. The results showed that the PCC content focused on providing information and opinions rather than expressing experiences of PCC in practice. Qualitative content analysis of 428 selected tweets revealed content on a vision that all care should be person‐centred but that the realization of that vision was more complicated. Conclusions: Twitter has shown to be a quick and non‐intrusive data collection tool for uncovering stakeholders' expressions concerning PCC. The PCC content revealed that stakeholders feel a need to 'educate' others about their perception of PCC when experiences and real‐life applications are missing. More action should be taken for the implementation of PCC rather than circulating PCC vision without operationalization in care. Public Contribution: The public provided the data through their posts on Twitter, and it is their perception of PCC that is studied here.